1977
DOI: 10.1086/jar.33.4.3629752
|View full text |Cite
|
Sign up to set email alerts
|

An Information Flow Model for Conflict and Fission in Small Groups

Abstract: Abstract. The paper is devoted to game-theoretic methods for community detection in networks. The traditional methods for detecting community structure are based on selecting denser subgraphs inside the network. Here we propose to use the methods of cooperative game theory that highlight not only the link density but also the mechanisms of cluster formation. Specifically, we suggest two approaches from cooperative game theory: the first approach is based on the Myerson value, whereas the second approach is bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
2,367
0
46

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 4,176 publications
(2,445 citation statements)
references
References 9 publications
32
2,367
0
46
Order By: Relevance
“…Zachary (1975Zachary ( , 1977 argued that when conflicts between rival leaders within a group are sufficiently intense, the group would segment through dissolution of the minimum number of links needed to separate into two. Anticipating our analysis of this case in Section IV, we take issue with this adhesionbased hypothesis for several reasons.…”
Section: C+ Hypotheses About Adhesionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zachary (1975Zachary ( , 1977 argued that when conflicts between rival leaders within a group are sufficiently intense, the group would segment through dissolution of the minimum number of links needed to separate into two. Anticipating our analysis of this case in Section IV, we take issue with this adhesionbased hypothesis for several reasons.…”
Section: C+ Hypotheses About Adhesionmentioning
confidence: 99%
“…When the edges of graphs are weighted, or we convert a weighted graph to an equivalent multigraph, we can make use of Ford and Fulkerson's (1956) It is this theorem that Zachary (1975Zachary ( , 1977 uses to partition his karate club network, whose leaders are in conflict, into two halves: those who are most adhesively connected (by the greatest number of edge-independent paths ϭ the least-edge cutset) with the club's administrator and those most adhesively connected to the club's karate instructor. We discussed this case in Section I.C, in which our critique of Zachary's adhesion-based minimum 30 Dirac (1960) showed that this result, in which each edge e has a numerical weight w~e!, is a straightforward corollary of Menger's Theorem B.…”
Section: Global Menger's Theorem Bmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that this strategy yields indeed pretty good solutions for some well known benchmark problems including Zachary's Karate Club [39] and the Chesapeake-Bay Food Web compiled by Baird and Ulanowicz [3]: For Zachary's Karate club, our method produced exactly the "historically correct" partition.…”
Section: The Basic Set-upmentioning
confidence: 80%
“…Figure 3 shows Orca's results, a clear success. The second example was compiled by Wayne Zachary [32] while doing a study on the social structure of friendship between the members of a university sports club. The two real-world factions are indicated by color in Figure 4.…”
Section: Parameters and Feasibilitymentioning
confidence: 99%